2012
DOI: 10.2478/s11687-012-0029-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of host-parasite interactions during the experimental Trichinella spiralis infection in pigs

Abstract: The aim of the present experiment was to assess the clinical, haematological, biochemical and immunological responses of pigs experimentally infected with Trichinella spiralis. One group of 6 pigs was infected with 1500 larvae/kg body weight and one group of 7, was maintained as control. The highest larval density was in the diaphragm (504.3 ± 8.2). During the experimental T. spiralis infection in pigs, increased values of total granulocyte number, eosinophils, blood glucose, K+ concentration, CK, ALT, AST and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…In high infection groups, peak blood glucose concentration was recorded 35–49 days post infection ( La Grange & Mukaratirwa, 2014 ). A significant increase in blood glucose concentration 30 days post infection was also reported in pigs ( Oltean et al, 2012 ) which coincided with trichinella larvae being established in the striated muscles of host.…”
Section: Introductionsupporting
confidence: 55%
“…In high infection groups, peak blood glucose concentration was recorded 35–49 days post infection ( La Grange & Mukaratirwa, 2014 ). A significant increase in blood glucose concentration 30 days post infection was also reported in pigs ( Oltean et al, 2012 ) which coincided with trichinella larvae being established in the striated muscles of host.…”
Section: Introductionsupporting
confidence: 55%
“…The study by Sukhdeo and Mettrick (1984) reported that the reduced absorptive capacity of the intestine cannot be a leading cause, since it has been reported that during moderate infection, Trichinella infection does not affect glucose uptake by intestine. However, a study by Oltean et al (2012) reported an increase in the blood glucose concentration of Trichinella spiralisinfected pigs 30 days post-infection comparative with uninfected ones. Therefore, this suggests that trichinellosis has an influence in glucose metabolism.…”
Section: Discussionmentioning
confidence: 91%
“…The levels of plasma ALB (albumin), and ALT (alanine aminotransferase), in Berkshires are significantly higher than those in Ningxiang pigs and F 1 offspring. The activity of ALT increases in pigs during bacterial infection, which helps to enhance disease resistance [27]. The increase in ALB levels can enhance the immunity of piglets [28].…”
Section: Discussionmentioning
confidence: 99%